PENGARUH RASIO KEUANGAN TERHADAP KINERJA KEUANGAN PADA BANK UMUM SWASTA NASIONAL DEVISA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013 – 2016 - Enyvia Purnomo, Untung Sriwidodo & Edi Wibowo (Universitas Slamet Riyadi, 2018)
This study aims to determine the CAR, NPL, NIM, BOPO and LDR against ROA. Types of data used in this study are Qualitative Data and Quantitative Data. The data source used in this research is obtained from the annual financial statements of Foreign Exchange Private National Banks listed on the Indonesia Stock Exchange during the period 2013 - 2016 published on the BEI website (www.idx.co.id). The population in this study were 35 Banks, the sampling technique used purposive sampling that is 16 banks. Data analysis techniques used classical assumption test, multiple linear regression analysis, t test, F test and coefficient of determination. The result of the research shows that: CAR has no significant effect on ROA, NPL has no significant effect on ROA, significant effect on ROA, BOPO has no significant effect on ROA and it can be seen that Capital Adequacy Ratio (CAR) Non-Performing Loan (NPL), Net Interest Margin (NIM), Operating Expenses to Operating Income (BOPO) and Loan to Deposit Ratio (LDR) have significant effect on Return On Assets (ROA). Keywords: CAR, NPL, NIM, BOPO, LDR, ROA